Estrous and pregnancy rate responses of postpartum Bali cattle to concentrate supplementation with different protein levels of rice-straw as basal ration. Issue 1 (April 2020) - Sonjaya, H; Rahim, L; Sari, D K; Abdullah, A; Gustina, S; Hasbi, H
Abstract: The aim of the research is to determine the effect of concentrate with different protein level rice straw as basal ration on the percentage of pregnancy rate of Bali cattle maintained on traditional farming system. The research was divided into two experiments. First experiment: a number of 46 cows divided into 4 treatment groups. Each group respectively protein level 0%, 10%, 12%, and 14%. Experiment 2: a number of 324 Bali cows postpartum got concentrate supplementation with different protein levels were divided into three groups, each got a protein level of 10%; 12%, and 14%. The rice straw diet given ad-libitum and concentrate as much as 1 kg per head per day for two months. Livestock that appears estrous after feeding directly mated naturally and partially performed artificial insemination. Pregnancy examinations carried rectal palpation and partly validated with ultrasound. The results showed that estrous respon in the first experiment not significantly affected by supplementation of concentrate with protein level for 10–14%. In contrast, estrous intensity was obviously visible in group treatment with 14% protein level. The supplementation of protein level in concentrate increased natural estrous 66.05% and natural mating generated 91.65% of pregnancy rate. However, 43.95% cows were artificially inseminated generating 81.63% of pregnancy rate. It's sonclude that supplementation of concentrate for feed Bali cows with rice straw as basal in the dry season caused increasing the percentage of postpartum estrous and highest of pregnancy rate.